Dermal penetration and resorption of beta-naphthylamine and N-phenyl-beta-naphthylamine from lubricants in an ex vivo human skin model. (October 2017) - Dennerlein, Kathrin; Göen, Thomas; Zobel, Melanie; Boos, Anja M.; Drexler, Hans; Kilo, Sonja
Abstract: Dermal Penetration of aromatic amines (AA's), often suspected or known to be carcinogenic, can play an important role in the overall human exposure. However, information on penetration of certain AA's is poor and inconsistent. Penetration of the former lubricant additive N -phenyl-beta-naphthylamine (PBNA) and its contaminant beta-naphthylamine (BNA) a known carcinogen was investigated and the influence of formulation and co-application characterized. Percutaneous penetration of BNA and PBNA through freshly excised human skin (n = 8; 48 h) was investigated using an ex vivo diffusion cell model. Both AA's were applied in a technical-conform lubricant or dissolved in hexane. The amount of BNA and PBNA applied to skin was 0.52 and 259 μg/0.64 cm 2 . The analytical determination of AA's was performed by GC-MS. Both, BNA and PBNA penetrated through human skin (38 vs. 5% of applied dose). In contrast to BNA, the percutaneous penetration of PBNA continued beyond the end of exposure. Co-exposure of both AA's increased the intradermal uptake of BNA and PBNA (p < 0.05). Exposure in lubricant showed the least overall penetration (2.9 and 1.9% of applied dose). The results clearly reveal that dermal penetration of both AA's depends strongly on the mode of application. Co-application and formulation alters the penetration of the AA's. Graphical abstract: Highlights: New insights into dermal uptake of environmental and occupational relevant AA's. Workplace exposure scenarios for investigation of dermal resorption of AA's ex vivo . For the first time intra- and transdermal penetration of PBNA has been shown. Characterization of dermal penetration of carcinogenic BNA through human skin. Formulation and co-exposure have a relevant impact on dermal uptake of both AA's.